800Exploration of the brain's white matter pathways with dynamic queries - Akers, D.; Sherbondy, A.; Mackenzie, R.; Dougherty, R.; Wandell, B. (2004 IEEE Visualization Conference, 2004)
Diffusion tensor imaging (DTI) is a magnetic resonance imaging method that can be used to measure local information about the structure of white matter within the human brain. Combining DTI data with the computational methods of MR tractography, neuroscientists can estimate the locations and sizes of nerve bundles (white matter pathways) that course through the human brain. Neuroscientists have used visualization techniques to better understand tractography data, but they often struggle with the abundance and complexity of the pathways. We describe a novel set of interaction techniques that make it easier to explore and interpret such pathways. Specifically, our application allows neuroscientists to place and interactively manipulate box-shaped regions (or volumes of interest) to selectively display pathways that pass through specific anatomical areas. A simple and flexible query language allows for arbitrary combinations of these queries using Boolean logic operators. Queries can be further restricted by numerical path properties such as length, mean fractional anisotropy, and mean curvature. By precomputing the pathways and their statistical properties, we obtain the speed necessary for interactive question-and-answer sessions with brain researchers. We survey some questions that researchers have been asking about tractography data and show how our system can be used to answer these questions efficiently.